Photo-remediation of phenanthrene contaminated soil under visible light irradiation - Chonlada Dechakiatkrai Theerakarunwong (2018)
© 2016, Chiang Mai University. All rights reserved. The photocatalytic degradation of phenanthrene-contaminated soil over Fe-doped TiO2under visible light irradiation was investigated. The influence of physicochemical parameters such as catalyst dosage, dopant doping and soil pH was studied. The optimum amount of 3 at. wt%Fe doped TiO2(1%) expressed high photocatalytic activity of 83.45% under visible irradiation with alkaline conditions within 2 h. The Fe dopant significantly enhanced phenanthrene photocatalytic degradation by the strong oxidizing OH·radical and complex [Fe3+-ligand] could generated by the Photo-Fenton-Like catalyst reaction. A possible mechanism of phenanthrene degradation was proposed based on GC/MS elucidation. In the presence of Fe dopant, phenanthrene was degraded to heptadecane. Based on the quantification analysis, the presence of TiO2catalysts for degradation of phenanthrene in the soil sample could reduce the concentration of phenanthrene from 60 mg kg-1to 20 mg kg-1within 2 hours, while in the control soil without catalyst, the concentration of phenanthrene could only be reduced from 60 mg kg-1to 40 mg kg-1in equal time.